Medical education in health: experience report in a symposium about women, family planning and reproductive rights, in the context of COVID-19 (Research, Society and Development, 2021)
During the social isolation resulting from the COVID-19 pandemic, one of the challenges is to continue, in an innovative way, to prepare teenagers for sexual life in a safe way, calling them to the responsibility of taking care of their own bodies to prevent unwanted situations such as contracting sexually transmitted diseases (STIs) or an unplanned pregnancy do not occur. In this sense, there was a need to create a technological space for interaction between expert professors and students at the São Lucas University Center (UniSL), in Porto Velho/Rondônia, and the local community in order to guide the counseling on definitive contraceptive methods, sexual rights, reproductive rights and women’s freedom, also an interactive session on myths and truths about contraceptive methods.